Temos a terra, e agora, somos livres? : um estudo sobre o processo organizativo no Projeto de Assentamento Nova Tangará – Uberlândia, MG - Vasconcellos, Inaê Soares de (2023)
The process by which people in the Nova Tangará rural settlement build (and deal with) their conditions of social and political organization and their socio-productive inclusion is the main theme of the work. With theoretical and historical support relating to the issue of land and ruralities in Brazil coming from the works of Ignácio Rangel, José de Souza Martins, Klaas Woortmann, José Graziano da Silva, Sérgio Sauer, Leonilde Medeiros, Bernardo Mançano Fernandes, and in epistemological consonance with Pierre Bourdieu in his notions of strategy, habitus and class, the following research question was elaborated: with land ownership, are subjects now autonomous? What is the content of this autonomy? The hypothesis is that most members of that settlement seek to maintain the highest possible levels of autonomy from the perspective of ownership. The idea of a settlement community, in this sense, would be a subjective inconvenience for most settlers; It would be better to have social recognition as a family farmer. A theoretical deepening was carried out, contained in the first chapter, identifying that land income, discussed by Ignágio Rangel, José de Souza Martins and José Graziano da Silva, is a fundamental category to understand the processes of individualization of subjects in their lots, difficulties in community organization and social and productive precariousness observed in the settlement. Regarding methodological aspects, the procedures were interviews, application of questionnaires and review of bibliography on the settlement in question. In the second chapter, the characteristics of the Movement that organized the occupation and the camp between 1999 and 2003 are discussed, as well as the relationships between that group, after the settlement was established, from 2004, and the settlers , observing the tension between property and autonomy inherent to this relationship. The third chapter seeks to identify and analytically elaborate the fundamental characteristics of autonomy/freedom and its relationship with the ownership of the lot for the settlers. In the fourth and final chapter, the most important discoveries of the work and the perspectives of community building are presented, as well as the challenges of this process.